2018
DOI: 10.3390/ijms19020507
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Metalloproteinase Inducer EMMPRIN (CD147) in Cardiovascular Disease

Abstract: The receptor EMMPRIN is involved in the development and progression of cardiovascular diseases and in the pathogenesis of myocardial infarction. There are several binding partners of EMMPRIN mediating the effects of EMMPRIN in cardiovascular diseases. EMMPRIN interaction with most binding partners leads to disease progression by mediating cytokine or chemokine release, the activation of platelets and monocytes, as well as the formation of monocyte-platelet aggregates (MPAs). EMMPRIN is also involved in atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 137 publications
(210 reference statements)
1
43
0
Order By: Relevance
“…The binding of CyPA to CD147 on the surface of platelets induces rapid degranulation and activation, leading to shape changes and the release of pro-inflammatory chemokines [4]. Furthermore, the CD147-CyPA interaction induces leukocyte chemotaxis and activation, expression of matrix-metalloproteinases, promotes atherosclerotic plaque formation, and plays critical roles in several inflammatory and cardiovascular diseases [14,[31][32][33]. CD147 has also been associated with other integrins, including α 3 β 1 and α 6 β 1 [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of CyPA to CD147 on the surface of platelets induces rapid degranulation and activation, leading to shape changes and the release of pro-inflammatory chemokines [4]. Furthermore, the CD147-CyPA interaction induces leukocyte chemotaxis and activation, expression of matrix-metalloproteinases, promotes atherosclerotic plaque formation, and plays critical roles in several inflammatory and cardiovascular diseases [14,[31][32][33]. CD147 has also been associated with other integrins, including α 3 β 1 and α 6 β 1 [2].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of cardiovascular diseases, CyPA induces leukocyte chemotaxis and adhesion, and 2 of 9 myocardial MMP expression, facilitating subsequent myocardial remodeling. Inhibition of extracellular CyPA significantly decreases platelet activation and thrombus formation as well as the formation of monocyte-platelet aggregates [4,7,8,13,14]. Furthermore, our group identified glycoprotein VI (GPVI) to be an adhesion-mediating partner for CD147 on the platelet surface, which is the first time it has been demonstrated that CD147 plays a direct role in cell adhesive events, apart from mediating adhesion via intracellular signaling, leading to the expression of adhesion molecules [11].…”
Section: Introductionmentioning
confidence: 90%
“…CD147 is a key player in the inflammation process [18,34,35]. Specific inhibition of CD147 with small interfering (si) RNA or monoclonal antibody (mAb) has been shown to exert profound anti-atherosclerotic effects, both in vitro and in vivo, through inhibition of CD147-mediated MMP-9 induction [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…CD147-evoked promotion of the inflammation cascade occurs through interactions with several ligands, including CypA and intergrins [35]. Previous studies have shown that interactions of CD147 with CypA recruit inflammatory cells to inflamed tissue with upregulation of MMP production, and are closely associated with cardiovascular diseases [18,38].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it was previously reported that EMMPRIN levels are strongly upregulated in VSMC of human non-syndromic TAA and its expression is induced in vitro by TGF-β and AngII [11][12][13]. Among EMMPRIN ligands important to be mentioned there are E-selectin, S100A9, and Cyclophilin A (CyPA) [14]. The latter is a peptidyl-prolyl cis-trans isomerase, object of several studies in the cardiovascular field [15,16].…”
Section: Introductionmentioning
confidence: 99%